Hospital Contracting Reforms : The Lebanese Ministry of Public Health Experience - Khalife, Jade (Taylor and Francis, 2017)
Since 2009, the Ministry of Public Health (MoPH) in Lebanon has been going through a major reform initiative to improve its contracting system with private and public hospitals. The private sector is the main provider of hospital care in the country and the main contractor to the MoPH for the provision of curative care. As an “insurer of last resort,” the MoPH plays an important role in providing hospital coverage to 53% of the population who lack coverage by private or public insurance schemes, through contractual arrangements with the private sector. Historically, the MoPH used hospital accreditation as the basis for contracting and for determining the reimbursement rate. However, recent studies by the MoPH showed that reimbursing hospitals solely on accreditation results was not appropriate and led to an unfair and inefficient reimbursement system. The reform program included the development of several components, in particular, an automated billing system, a utilization review function, standardized admission criteria, and a hospital case mix index that accounts for case complexity. In 2014, the MoPH started implementing a new mixed-model contracting system with private and public hospitals. Preliminary evaluation of the new model suggests that the system incentivized hospitals to admit fewer inappropriate cases and more cases that are more complex/serious. This article shares one experience of how to introduce a merit-based system to face the common practice of political clientelism and confessional/religious-based favoritism in Lebanon. It highlights the importance of stakeholder engagement in a framework of networking and participatory governance that proved to be a key element behind the resilience of a diversified health system.